Lipedema subsequent with lymphedema and obesity in male patient: a rare case - Alim, Sonia C.; Suryana, Ketut (International Journal of Research in Medical Sciences, 2022)
Lipedema is a disorder of abnormal subcutaneous fat deposition which almost exclusively occured in women. It is an unusual case that happens in male patients. Lipedema is often misdiagnosed to obesity and lymphedema. In case at hand, a 39-year-old obese male (body mass index of 54.3 kg/m2) presented bilateral non-pitting edema from buttocks to knees, palpable fat tissue nodules, pain at pressure, positive cuff sign, negative Stemmer-Kaposi sign, hyperpigmentation and thickened skin along the calves, and minimal responds to compression therapy. Average blood pressure was 145/90 mmHg. Laboratory studies were unremarkable, except leukocytosis and increased erythrocyte sedimentation rate which might be related to obesity-associated leukocytosis. Diagnosis of type III lipedema subsequent with lymphedema, grade III obesity, and mild hypertension was made. The patient subsequently reported an improvement of the complaints after receiving nonsteroidal anti-inflammatory drug, proton pump inhibitors, and antihypertensive. Weight loss was encouraged as initial steps to reduce aggravating risks of obesity. This case underlines that lipedema needs to be considered as a differential diagnosis in male patients.